Nidal Guessoum Perspective on A Logical Synthesis Between Science And Islam - Huda, Muhammad Muchlish; Habibi, Debi Fajrin (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2022)
In this modern era appeared the modern thinker of Muslims who are trying to respond to the development of modern science with different points of view such as Zia Eddin Sardar, Seyyed Hossein Nasr and others. One such modern Muslim thinker is Nidal Guessoum. Through his book Islam's Quantum Question: Reconciling Muslim Tradition and Modern Science, the author attempted to reconcile Islam and science, which have been in conflict with each other in terms of the truth of knowledge since time immemorial. Islam believes that the source of reality of knowledge is the text (the Qur’an and Hadith), and science believes that the source of reality of knowledge is the mind. Through this launch, Nidal researched in-depth and integrative research on the position of Islam in looking at science, and most of his research revolves around natural sciences such as physics, development theory, global principles (Antropik Principle, Philosophy of Modern Science) and other natural sciences. With his accurate and profound background in the beauty of physical science and astronomy, Nidal presented some philosophical questions about the universality of the modern world, either from the perspective of philosophy or from the perspective of applied sciences.